Premotor antidepressants use differs according to Parkinson's disease subtype: A cohort study. (June 2021) - D'Alessandro, Roberto; Zenesini, Corrado; Baldin, Elisa; Bonavina, Giuseppe; Calandra-Buonaura, Giovanna; Cortelli, Pietro; Fabbri, Giovanni; Guarino, Maria; Nassetti, Stefania Alessandra; Pantieri, Roberta; Samoggia, Giuseppe; Nonino, Francesco; et al.
Abstract: Background: Depression is more frequently associated with akinetic-rigid/postural instability gait difficulty subtypes of Parkinson's disease than with tremor-dominant subtype. Objectives: The aim of the study is to investigate the frequency of exposure to antidepressant drugs, as proxy of depression, before motor onset according to Parkinson's disease subtypes. Method: Based on a historical cohort design, the exposure to antidepressant drugs before Parkinson's disease motor onset was obtained from the drug prescription database and assessed in the resident population of the Local Healthcare Trust of Bologna (443, 117 subjects older than 35 years). Diagnosis of Parkinson's disease and subtype (tremor dominant, non-tremor dominant) at onset were recorded by neurologists and obtained from the "ParkLink Bologna" record linkage system. Exposure to antidepressants was compared both to the general population and between the two subtypes. Results: From 2006 to 2018, 198 patients had a tremor dominant subtype at onset whereas 450 did not. Comparison with the general population for antidepressant exposure showed an adjusted hazard ratio of 0.86 (95% CI 0.44–1.70) for the tremor dominant subtype and 1.66 (1.16–2.39) for the non-tremor dominant subtype. Comparison of non-tremor dominant with tremor dominant subtypes showed an adjusted odds ratio of 1.86 (1.05–3.95) for antidepressant exposure. Conclusions: In our study, non-tremor dominant Parkinson's disease at onset was significantly associated with exposure to antidepressants in comparison to the general population and in comparison with the tremor dominant subtype. These results support the hypothesis of different biological substrates for different Parkinson's disease subtypes even before motor onset. Highlights: Depression is more frequent in the non-tremor Parkinson's disease subtype. Whether depression before motor onset varies in PD subtypes is unknown. We found an association with premotor antidepressants use and non-tremor subtype. Our results support different pathophysiology for Parkinson's disease subtypes.